6(x+10)(x-8)=0

Simple and best practice solution for 6(x+10)(x-8)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x+10)(x-8)=0 equation:


Simplifying
6(x + 10)(x + -8) = 0

Reorder the terms:
6(10 + x)(x + -8) = 0

Reorder the terms:
6(10 + x)(-8 + x) = 0

Multiply (10 + x) * (-8 + x)
6(10(-8 + x) + x(-8 + x)) = 0
6((-8 * 10 + x * 10) + x(-8 + x)) = 0
6((-80 + 10x) + x(-8 + x)) = 0
6(-80 + 10x + (-8 * x + x * x)) = 0
6(-80 + 10x + (-8x + x2)) = 0

Combine like terms: 10x + -8x = 2x
6(-80 + 2x + x2) = 0
(-80 * 6 + 2x * 6 + x2 * 6) = 0
(-480 + 12x + 6x2) = 0

Solving
-480 + 12x + 6x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '6'.
6(-80 + 2x + x2) = 0

Factor a trinomial.
6((-10 + -1x)(8 + -1x)) = 0

Ignore the factor 6.

Subproblem 1

Set the factor '(-10 + -1x)' equal to zero and attempt to solve: Simplifying -10 + -1x = 0 Solving -10 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -1x = 0 + 10 Combine like terms: -10 + 10 = 0 0 + -1x = 0 + 10 -1x = 0 + 10 Combine like terms: 0 + 10 = 10 -1x = 10 Divide each side by '-1'. x = -10 Simplifying x = -10

Subproblem 2

Set the factor '(8 + -1x)' equal to zero and attempt to solve: Simplifying 8 + -1x = 0 Solving 8 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -1x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -1x = 0 + -8 -1x = 0 + -8 Combine like terms: 0 + -8 = -8 -1x = -8 Divide each side by '-1'. x = 8 Simplifying x = 8

Solution

x = {-10, 8}

See similar equations:

| 7x-2y=-10 | | 7t+1/5=t+6/10+t-4/10 | | (5x-8)/(x+6) | | -6x+4=-3x+16 | | 113-4x=14x+15 | | -343=-7(1+6x) | | 7d+(5-8)d+11d= | | 4(6-3x)=36 | | 2x^2+3=9 | | 80-4x=14-8x | | -9t-9=9 | | 104/6 | | -1/9(x-27)+1/6(x+6)=x-7 | | 2x^2-15x-16=-11-24x | | 32-16=4x-28 | | y=x^2+8 | | 35+3y-15=14y-10-5y | | 2x-7=2(x-4)+1 | | 6x-48=4x-14 | | X+20+4x=-28-4x-33 | | X^4-5x^2-24=0 | | -4+2x-x=x-5+x | | -10x-50+66=-17-17 | | 104/8 | | 32=-6(v-4)-2(7v-4) | | 28x-12=29x | | 10x-7y+3-2y+4x= | | -42-(-19)=9x | | 5(2x-1)=3(x+2) | | x/4-x/6=8 | | 120=10+5x | | 3(3x-9)=40 |

Equations solver categories